EFEKTIVITAS APLIKASI QUIZIZZ TERHADAP HASIL BELAJAR SISWA PADA KELAS IV SDN BAJULAN - Aulia, Dini Dwi; Melik Budiarti; Naniek Kusumawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
IPAS learning is learning that most often uses learning media to support the process of delivering information to students better. However, in each field, many students get below average scores in IPAS lessons, one of which is the use of inappropriate learning media. This study uses a quantitative method with a quasi-experimental model to see if the use of the Quizizz Application is effective for improving student learning outcomes in IPAS lessons. Based on the results of data analysis of research implementation activities carried out to see the effectiveness of the Quizizz Application on the learning outcomes of grade IV students at SDN Bajulan, it can be concluded that the implementation of the research carried out went well. This can be proven by the increase in learning outcomes in grade IV students of IPAS material. the implementation of research in the control class without using treatment with learning outcomes showed numbers 60-85 with the average score obtained by students was 68, then treatment in the experimental class at the third meeting showed an increase in learning outcomes with a score of 70-90 with an average student score of 78.